IDENTIFIKASI MORFOMETRIK DAN MERSITIK BETTA BURDIGALA ASAL PERAIRAN BANGKA SELATAN SEBAGAI DASAR PENGEMBANGAN AKUAKULTUR - GULO, CANIA PUTRI NIMALASARI; WIJAYANTI, AMALIA; MADYASTUTI, EKA PUTRI; SYARIF, AHMAD FAHRUL (Universitas Mahasaraswati K. Mataram, 2023)
Betta burdigala is a type of endemic fish from Bangka Island. The Betta burdigala on Bangka Island is threatened with extinction, with Critically Endangered (CR) status. The decline in the Betta burdigala fish population is caused by habitat degradation and environmental damage. The existence of Betta burdigala fish has never been reported in waters other than Bangka Island. This research aimed to described the morphometric and meristic characteristics of Betta burdigala fish from South Bangka waters as a basis for the conservation and development of aquaculture. The method used in this research is observation, with direct measurement, and observation of morphometric and meristic characters as well as literature studies to identify the morphology of Burdigala betta. The results of this research showed that the morphological characters of Betta burdigala have a mixed form. The shape of the tail fin of the Betta burdigala is round (spherical).. This type of fish's mouth is terminal (located in the anterior middle of the head). The type of scales it has is cosmoid shaped. The average morphometric characters measured were TL(28.25mm), SL(22.05mm), HL(6.15mm), ED(1.5mm), IW(1.6mm), BD(3.8mm), PDL(1.3mm), DBL(7.6mm), DFH(5.8mm), PAL(9.2mm), ABL(10.85), CPD(3.25mm), LUCL(5mm), LMCL(4 .5mm), LCLL(4.1mm). The average meristic character of the Betta burdigala fish is that the dorsal fin rays have the formula D.XIV, the anal fin rays have the formula A.XXV. The caudal fin radius has the formula C.XIII.